Rheological behavior study and its significance in the assessment of application properties and physical stability of phytosome loaded hydrogels - Djekić, Ljiljana; Krajišnik, Danina (Archives of Pharmacy, 2021)
Phytosomes are amphiphilic molecular complexes of substances of plant origin and phospholipids that are considered as active ingredients of dermopharmaceutical and cosmetic formulations of potentially improved efficiency. The study aim was the formulation of carbomer hydrogels with commercially available phytosomes of escin (Escin ß-Sitosterol Phytosome®) (EP) and 18-ß glycyrrhetinic acid (18-ß Glycyrrhetinic Acid Phytosome®) (GP) and evaluation of their application properties and real-time physical stability. Phytosomes incorporation did not significantly affect pH of the hydrogels, which was acceptable for cutaneous application. However, these hydrogels had significantly different organoleptic properties (opaque and softer consistency) compared to the hydrogel without active substance (C) and the hydrogels with pure active substances (E and G) used for comparison. The values ​​of maximum and minimum apparent viscosity and yield stress were significantly lower in phytosome-loaded hydrogels. The results of oscillatory rheological analysis indicated that viscous character prevails in EP and GP hydrogels (elastic modulus (G ')˂viscous modulus (G ")), while in hydrogels C, E and G elastic properties were more pronounced (G'˃G "). Escin phytosome had greater influence on carbomer gel network strength. Phytosome-loaded hydrogels were physically stable during 24 months of storage under ambient conditions, although the rheological analysis also indicated a potential risk of sedimentation.
Keywords: Phytosomes; hydrogel; rheological characterization; application properties; physical stability